2017
DOI: 10.1038/s41598-017-10925-7
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression in lung cancer and its correlation with driver mutations: a meta-analysis

Abstract: Although many studies have addressed the prognostic value of programmed cell death-ligand 1 (PD-L1) expression in lung cancer, the results remain controversial. A systematic search of the PubMed, EMBASE, and Cochrane Library databases was performed to identify the correlation between PD-L1 expression and driver mutations and overall survival (OS). This meta-analysis enrolled a total of 11,444 patients for 47 studies, and the pooled results showed that increased PD-L1 expression was associated with poor prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
174
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(203 citation statements)
references
References 81 publications
22
174
7
Order By: Relevance
“…We also found correlations between tumoral PD‐L1 expression status and histopathological features: PD‐L1 expression was more frequent in tumours of the biliary epithelial type and in those with poor histological differentiation. An association between PD‐L1 expression and high histological grade has been previously reported in lung cancers …”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…We also found correlations between tumoral PD‐L1 expression status and histopathological features: PD‐L1 expression was more frequent in tumours of the biliary epithelial type and in those with poor histological differentiation. An association between PD‐L1 expression and high histological grade has been previously reported in lung cancers …”
Section: Discussionmentioning
confidence: 65%
“…An association between PD-L1 expression and high histological grade has been previously reported in lung cancers. 30 Regarding immune cell PD-L1 expression, 65% of cases showed PD-L1-positive immune cell infiltration when the 22C3 assay was used, and there was a significant association between tumour cell PD-L1 expression status and immune cell PD-L1 expression status. Although the clinical implications of PD-L1 expression in immune cells have yet to be established in most other tumours, higher response rates for atezolizumab have been reported for bladder cancers with PD-L1-positive immune cells, evaluated with the SP142 assay.…”
Section: Discussionmentioning
confidence: 93%
“…Our previous study showed that PD-L1 overexpression correlated with poor prognosis in breast cancer 6 , gastric cancer 7 , and lung cancer 8 . However, the relationship between PD-L1 expression and NHL is controversial.…”
Section: Introductionmentioning
confidence: 97%
“…PD‐L1 expression has been observed to correlate with some clinicopathologic features, including smoking, an advanced tumor stage, and squamous cell carcinoma histology . However, other studies have failed to demonstrate such associations .…”
Section: Discussionmentioning
confidence: 99%
“…13,18 Some studies have observed that high PD-L1 expression is associated with smoking, an advanced stage, squamous morphology, and molecular alterations, including epidermal growth factor receptor (EGFR), Kirsten rat sarcoma viral oncogene homolog (KRAS), and anaplastic lymphoma kinase (ALK ) oncogenic mutations, whereas other studies have shown conflicting results. 5,11,13,15,[19][20][21][22][23][24][25] These conflicting data may be caused by differences in population cohorts, PD-L1 antibodies, PD-L1 expression cutoff values, specimen types (whole sections or tissue microarrays), and so forth.…”
Section: Introductionmentioning
confidence: 99%